2008
DOI: 10.1172/jci34174
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chondrogenesis and chondrocyte differentiation by stress

Abstract: Chondrogenesis and endochondral ossification are the cartilage differentiation processes that lead to skeletal formation and growth in the developing vertebrate as well as skeletal repair in the adult. The exquisite regulation of these processes, both in normal development and in pathologic situations, is impacted by a number of different types of stress. These include normal stressors such as mechanical loading and hypoxia as well pathologic stressors such as injury and/or inflammation and environmental toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
174
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(182 citation statements)
references
References 114 publications
1
174
0
7
Order By: Relevance
“…Although our data show that the dissolved oxygen in the experimental containers was close to that measured in the control containers, both being normoxic, and that experimental tadpoles can swim to the surface to take oxygen, the possibility that a decrease in dissolved oxygen can be responsible of the described effects remains. Hypoxia has been considered a major stressor (Zuscik et al, 2008) and it has been proposed that tadpoles living in severely hypoxic water suffer from metabolic suppression (or a controlled reduction), which may produce a standby in their development (Wakeman and Ultsch, 1976;Feder and Wassersug, 1984;Ultsch et al, 1999). Our experimental results show that tadpoles raised in agar reach the final developmental stages in a similar time compared with the control ones, and thus no standby is observed.…”
Section: Discussionmentioning
confidence: 99%
“…Although our data show that the dissolved oxygen in the experimental containers was close to that measured in the control containers, both being normoxic, and that experimental tadpoles can swim to the surface to take oxygen, the possibility that a decrease in dissolved oxygen can be responsible of the described effects remains. Hypoxia has been considered a major stressor (Zuscik et al, 2008) and it has been proposed that tadpoles living in severely hypoxic water suffer from metabolic suppression (or a controlled reduction), which may produce a standby in their development (Wakeman and Ultsch, 1976;Feder and Wassersug, 1984;Ultsch et al, 1999). Our experimental results show that tadpoles raised in agar reach the final developmental stages in a similar time compared with the control ones, and thus no standby is observed.…”
Section: Discussionmentioning
confidence: 99%
“…4B). Quantitative PCR analysis revealed that markers for mature chondrocytes (40), such as COL10A1, VEGFA, RUNX2, and MMP13, were induced stronger in FOP-3DCI pellets than in resFOP-3DCI pellets (Fig. 4C and SI Appendix, Fig.…”
Section: Enhanced Chondrogenesis Of Fop-imscs Via Bmp and Tgf-β Signamentioning
confidence: 99%
“…Importantly, the fetal skeletal system is more sensitive to GBP during organogenesis in different animal models such as rats [67], mice [68,69] and chick [70]. GBP or VPA can cross the placenta and accumulate in several fetal organs delaying the osteogenesis and chondrogenesis [71][72][73][74][75][76][77]. These variations might be attributed to GBP or VPA can alter the maternofetal mineral and trace elements [78].…”
mentioning
confidence: 99%